Microeconometrics - Durlauf, Steven N.; Blume, Lawrence (The new Palgrave economics collection, 2010)
Due to demand from the economics community these books address key subject areas within the field. Each title is comprised of specially selected articles from the Dictionary and covers a fundamental theme within the discipline. All of the articles have been specifically chosen by the editors of the Dictionary, Steven N. Durlauf and Lawrence E. Blume and are written by leading practitioners in the field. The Collections provide the reader with easy to access information on complex and important subject areas, and allow individual scholars and students to have their own personal reference copy.